Gender Wage Differentials: New Cross-Country Evidence - Tim Callan; S. Adams; Nina Smith; Shirley Dex; Siv Gustafsson; Jürgen Schupp (Luxembourg Income Study (LIS), 1995)
This paper compares the most commonly quoted female-to-male wage ratios (based on hourly earnings in manufacturing) and ratios based on a harmonized analysis of household surveys. The surveys include employees of all types in all sectors - thereby overcoming the problems associated with a lack of comprehensive coverage and differences in definition. Countries studies include Sweden, Australia, Denmark, Germany, the United Kingdom, and Ireland. The article then adjusts wage ratios for differences in educational qualifications and labor market experience, using a human capital specification of the wage equation. The authors conclude that the extent of the wage gaps between countries may be overstated by the figures based on workers in manufacturing: figures based on harmonized analysis of household surveys find some degree of convergence around a higher central tendency. Wage ratios adjusted for educational qualifications and years worked converge even more around a higher mean.
Keywords: 330; Lohnstruktur; Schweden; Australien; Dänemark; Deutschland; Großbritannien; Irland